Quantification of methamphetamine in seized tablets by gas chromatography- flame ionisation detector - Roslan, Nor Syafiatul Fitri (2025)
Methamphetamine, is a drug function as a stimulant that affect the central nervous system. It has become a significant global concern due to its widespread abuse and dangerous health effects. This study focused on the quantification of methamphetamine in seized tablet samples from Kelantan, Malaysia, using gas chromatography coupled with flame ionisation detector (GC-FID). Methamphetamine quantification is critical for judicial processes, as the drug’s quantity directly affects the severity of legal charges. In this study, chromatographic separation was performed on a HP-5 MS column (30 m x 320 μm x 0.25 μm) with a temperature programme of 70 °C for 2 min, followed by a ramp up at 20 °C/min to 280 °C for 2 min with purified nitrogen as the carrier gas at a flow rate of 1.0 mL/min. The method was found to be satisfactory and successfully applied for quantification of methamphetamine samples with analysis time of 14.5 min. The GC-FID method was validated by assessing its linearity, limit of detection (LOD), limit of quantification (LOQ), precision, and accuracy. Calibration curves ranged 1.95 - 1000 μg/mL, established a correlation coefficient of 0.9976. Limit of detection and limit of quantification were 0.293 μg/mL and 0.975 μg/mL respectively. The precision test showed %RSD value below 2%. The accuracy test showed percentage recovery between 85 - 106 %. Quantification analysis of 155 methamphetamine samples indicated purity with range of 0.5 - 30.6%. This simple method was suitable for forensic routine analysis, especially in quantifying the methamphetamine from seized samples.